1997
DOI: 10.1897/1551-5028(1997)016<0384:cotmst>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Marine Screening Tests and Four Oslo and Paris Commission Procedures to Evaluate Toxicity of Offshore Chemicals

Abstract: Abstract-The results from the screening toxicity tests Artemia salina, Microtox, and Mitochondria RET test were compared with those obtained from OSPAR (Oslo and Paris Commissions)-authorized procedures for testing of offshore chemicals (Skeletonema costatum, Acartia tonsa, Abra alba, and Corophium volutator). In this study 82 test substances (26 non-water soluble) were included. The Microtox test was found to be the most sensitive of the three screening tests. Microtox and Mitochondria RET test results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Most samples were toxic to the gametes and embryos of H. tuberculata and the sea urchin tests were most sensitive across most leachates. As highlighted in the comparative assessment of the four tests (Binet et al 2003;Byrne et al 2003), bacterial luminescence and submitochondrial particle function were most sensitive to leachates with a high content of organic chemicals, a feature characteristic of these tests (Weideborg et al 1997;Argese et al 1998;Qureshi et al 1998). The large standard deviations in the EC50s for each site (Table 2) reflect the marked temporal variation in site sample chemistry (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most samples were toxic to the gametes and embryos of H. tuberculata and the sea urchin tests were most sensitive across most leachates. As highlighted in the comparative assessment of the four tests (Binet et al 2003;Byrne et al 2003), bacterial luminescence and submitochondrial particle function were most sensitive to leachates with a high content of organic chemicals, a feature characteristic of these tests (Weideborg et al 1997;Argese et al 1998;Qureshi et al 1998). The large standard deviations in the EC50s for each site (Table 2) reflect the marked temporal variation in site sample chemistry (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, none of the tests were consistently sensitive to all samples (statistical comparison in Byrne et al 2003), illustrating the importance of using a battery of tests for monitoring the toxicity of complex mixtures. Although generally less sensitive, bacterial luminescence and submitochondrial particle function are useful as rapid tests for day-to-day monitoring of toxicity (Weideborg et al 1997;Qureshi et al 1998;Argese et al 1998). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, it is normally easy to obtain many individuals starting from commercial cysts. In spite of this, to date the employment of Artemia is controversial particularly owing to its supposed inadequate sensitivity (Weideborg et al, 1997;Davoren et al, 2005). Otherwise, recent studies indicated that the evaluation of survival in Artemia in long-term toxicity tests is an useful and sensitive parameter (Brix et al, 2003(Brix et al, , 2004Manfra et al, 2009).…”
Section: Marine Crustaceansmentioning
confidence: 99%
“…than other acute toxicity tests (Weideborg et al, 1997) and can be used for the prediction of chemical toxicity in other aquatic organisms (Chen & Que Hee, 1995;Zhao et al, 1995). V. fischeri is a Gram-negative, rod-shaped, flagellate, heterotrophic bacterium recovered in marine ecosystem, with bioluminescence capability (Fig.…”
Section: A) B) C)mentioning
confidence: 99%